Beauty Standard as a Construction of Woman Objectification in Trisha R. Thomas’s Nappily Ever After - Sayekti, Heri Okta; Fitria, Sari (SULUK : Jurnal Bahasa, Sastra, dan Budaya, 2022)
The study aimed to depict how the beauty standards construct female objectification in Nappily Ever After and to analyze how the main character struggled toward beauty standards in the Nappily Ever After novel. This study is sought with qualitative methods to reveal the novel's issue. This study applied the theory of beauty myth from Naomi Wolf. The result of the study found that the beauty ideal is a woman who has straightened hair, brightening skin, a tall, slim body, and a pointed nose. Those highlighted Venus’s physical appearance which made her seem to be a typical woman and objectified her to conform to beauty standards. The study concluded that Venus internalized the beauty ideal which made her feel restricted by her looks and resulted in body image dissatisfaction. Venus struggled after she cut her hair which made her become an outcast in beauty image, being invisible by men, dismissal, and judged by people.